SISTAQUIT: training health care providers to help pregnant Aboriginal and Torres Strait Islander women quit smoking. A cluster randomised controlled trial. Issue 1 (3rd July 2022) - Gould, Gillian S; Ryan, Nicole M; Kumar, Ratika; Stevenson, Leah C; Carson‐Chahhoud, Kristin V; Oldmeadow, Christopher; Foster, Joley; Deeming, Simon; Boydell, Katherine; Doran, Christopher M; Searles, Andrew; Mattes, Joerg; et al.
Abstract: Background : About 44% of Indigenous Australian women smoke during pregnancy, compared with 12% of pregnant non‐Indigenous women. Health care providers can assist smoking cessation, but they are not typically trained in culturally appropriate methods. Objectives : To determine whether a health care worker training intervention increases smoking cessation rates among Indigenous pregnant smokers compared with usual care. Methods and analysis : Supporting Indigenous Smokers to Assist Quitting (SISTAQUIT) study is a multicentre, hybrid type 1, pragmatic, cluster randomised controlled trial that compares the effects of an intervention for improving smoking cessation by pregnant Indigenous women (16 years or older, 32 weeks' gestation or less) with usual care. Twenty‐one health services caring for Indigenous people in five Australian jurisdictions were randomised to the intervention (ten sites) or control groups (eleven sites). Health care providers at intervention sites received smoking cessation care training based on the ABCD (ask/assess; brief advice; cessation; discuss psychosocial context) approach to smoking cessation for Indigenous women, an educational resource package, free oral nicotine replacement therapy for participating women, implementation support, and trial implementation training. Health care providers in control group services provided usual care. Primary outcome: abstinence from smoking (self‐reported abstinence via survey, validated by carbon monoxide breath testing when possible) four weeks after enrolment in the study. Secondary outcomes: health service process evaluations; knowledge, attitudes, and practices of health care providers; and longer term abstinence, perinatal outcomes, and respiratory outcomes for babies (to six months). Ethics approval : The human research ethics committees of the University of Newcastle (H‐2015‐0438) and the Aboriginal Health and Medical Research Council of NSW (1140/15) provided the primary ethics approval. Dissemination of results : Findings will be disseminated in peer‐reviewed publications, at local and overseas conferences, and via public and social media, and to participating health services in art‐based formats and reports. Policy briefs will be communicated to relevant government organisations. Trial registration : Australia New Zealand Clinical Trials Registry, ACTRN12618000972224 (prospective).